Is American Teacher Education Fully Up to the Common Core Requirements? - Murray, Frank B. (Kappa Delta Pi record, 2014)
This narrative considers how well equipped today's teacher education students and faculty are to meet the demands of the new Common Core State Standards. Data from the Teacher Education Accreditation Council's national evaluation of teacher education programs gives a mixed picture that, while mostly encouraging, also reveals that some future teachers, current teacher education faculty, and cooperating teachers have misguided and worrisome views of their subject matter and pedagogy.